Fiber morfological properties of Kenaf (Hibiscus cannabinus) / Abdulrahman Sultang - Sultang, Abdulrahman (2005)
The fiber morfological properties of Kenaf (Hibiscus cannabinus) were studied to compare between stem portions and branch portion. The properties of concerned as fiber fiber length, fiber diameter and cell wall thickness. Parameters leading to paper properties were also as certain such as runkle ratio, felting power and coefficient of suppleness. The result indicated that most properties are higher in stem than branch. Thus, stem possess better morfological properties than branch and can lead to better potential for paper making.